Anxiety and Depression Associated with Anal Sexual Practices among HIV-Negative Men Who Have Sex with Men in Western China - Jiaxiu Liu (International Journal of Environmental Research and Public Health, 2020)
This study aimed to explore the prevalence and influencing factors of anxiety and depression among human immunodeficiency virus negative (HIV-negative) men who have sex with men (MSM) based on anal sex roles, so as to provide a scientific basis for the management of mental health conditions. Data were obtained from the baseline in a cohort study with a two-year follow-up period in western China. The Self-Rating Anxiety Scale and Center for Epidemiological Studies Depression Scale were used to assess anxiety and depression symptoms, respectively. The prevalence of anxiety and depression in 1771 MSM was 26.03% and 37.83%. Among them, 182 anal sex role “0” MSM who only had receptive anal sex with men reported the highest prevalence of anxiety and depression (31.32% and 46.15%), 467 anal sex role “1” MSM who only had insertive anal sex with men (22.27% and 32.76%), and 1122 anal sex role “0.5” MSM who engaged equally in both insertive and receptive anal sex intercourse with men (26.74% and 38.59%), respectively. Logistic regression analysis revealed that the influencing factors of anxiety include anal sex role “0”/”0.5”, low educational level, female sexual partners, frequently searching partners on the Internet, sexually transmitted diseases (STD) diagnosed by doctors, and no HIV counseling. Anal sex role “0”/”0.5”, rural area, casual male partners, female partners, STD diagnosed by doctors, frequently searching partners on the Internet, no HIV counseling, no condom use, and daily alcohol use were found to be associated with depression. In conclusion, early identification and intervention of anxiety and depression symptoms in HIV-negative MSM should be carried out, especially for anal sex role “0” MSM. Furthermore, key intervention and psychological counseling should be taken into consideration for MSM with a low education level, high-risk behaviors, and high-risk perceptions.